(untitled) - Zeghbroeck, Van Bart (2011)
The current gain capability of a Field-Effect-Transistor (FET) is easily explained by the fact that no gate current is required to maintain the inversion layer and the resulting current between drain and source. The device has therefore an infinite current gain in DC. The current gain is inversely proportional to the signal frequency, reaching unity current gain at the transit frequency
Vật lý bán dẫn
Keywords: Electrical engineering,Kỹ thuật điện; Materials.,Vật liệu.